Feed and Fodder Availability and Utilization Pattern in UrbanPeri-Urban Dairy Farms in and Around Navsari City of South Gujarat - Rathva, AL; sorthiya, LM; Gadhvi, DN; Patel, NB (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
This investigation was carried out to study the fodder resource management practices followed by selected 40 commercial dairy farmersin and around Navsari city of South Gujarat. The required information was collected through personal interview. Data analyzed revealedthat buffalo consisted more than two third of total strength. Population of younger animals like calves and heifers were 33 and 9 % oftotal herd strength, respectively. The annual green and dry fodder availability calendar showed that 95 % farmers used sugarcane topduring November to March. During April to July 100 % respondents fed whole sugarcane, whereas during August to October 34, 15and 4 farms were using green grass, green sorghum and green maize, respectively. Among dry fodder, paddy straw was popular andused by 37 farms, whereas 10 farms were using sorghum straw. The quantity of fodder used by each farm revealed that sugarcane topsfulfilled average 39.27 % of ration requirement in 38 farms. Similarly, green sugarcane fulfilled average 23 % of ration requirement in all40 farms. Green cut and carry grass fulfilled 13.15 % of ration in 34 farms. As far as dry fodder was concerned, paddy straw and sorghumstraw were used to fulfill 41.49 and 31.70 % of their ration requirement in farms, where it was used. Among concentrates cotton seedcake, wheat bran and compound concentrate (Sumul Dan) were used by 38, 20 and 16 farms, respectively. They were using cotton seedcake at proportion of 33% in their ration. Analysis of demand and supply of feed and fodder resources revealed that all farms studiedtogether required annually 10124, 2248 and 2248 tons of green fodder, dry fodder and concentrate as per thumb rule feeding of drymatter at 3 % of body weight. However, all feed resources were in shortfall by 21-51 %. Annual shortage of dry fodder was the highest,i.e., 51.33 % and shortage of concentrate was the lowest (14.64 %).
Keywords: Commercial dairy farm; Feed resources; North Gujarat; Peri-urban; Urban farms